EFFECTIVENESS OF USING EDUCATIONAL GAME-BASED SCIENCE MEDIA PRODUCTS IN IMPROVING SCIENCE LITERACY IN ELEMENTARY SCHOOL - Khairunnisak (CV Naskah Aceh, 2024)
This study examines the effect of using educational game-based science media products on improving science literacy , especially in terms of critical thinking or problem-solving skills in elementary school students. Through an experimental research design, the results showed a significant increase in the aspects of science literacy studied in the group of students who used educational game media compared to the control group. The results showed a significant increase in the aspects of science literacy studied in the experimental group. These findings indicate that the use of educational games can be an effective method for improving high-level thinking skills in students, such as critical thinking and problem solving. This study emphasizes the importance of integrating educational games into the elementary education curriculum to support the development of science literacy in more depth. In addition, these results also open up further opportunities for research related to the effectiveness of educational games in various other aspects of education.